Photovoltaic adhesive film with low shrinkage and preparation method thereof
Through the photovoltaic adhesive formula with specific component ratios, the synergistic effect of composite light stabilizer and composite modifier is used to solve the problems of high shrinkage rate, poor aging resistance and mechanical properties of photovoltaic adhesive films, and low shrinkage rate, The adhesive film with excellent mechanical properties and aging resistance extends the service life of photovoltaic modules and improves power generation efficiency.
Patent Information
- Application Number
- CN202411056970.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing photovoltaic adhesive film has high shrinkage rate, poor aging resistance and mechanical properties, which affects the power generation efficiency and service life of photovoltaic modules.
Photovoltaic film formulations with specific component ratios, including ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer, crosslinking agent, silane coupling agent, composite light stabilizer and composite modifier, through composite light stabilizer and composite The synergistic effect of modifiers improves the aging resistance and mechanical properties of the adhesive film and reduces the shrinkage rate.
The low shrinkage rate, excellent mechanical properties and aging resistance of the photovoltaic adhesive film are achieved, extending the service life of the photovoltaic module and improving the power generation efficiency.
Smart Images

Figure BDA0004976722190000031 
Figure BDA0004976722190000041 
Figure BDA0004976722190000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic adhesive film preparation, and in particular relates to a photovoltaic adhesive film with a low shrinkage rate and a preparation method thereof. Background Art
[0002] As the global demand for renewable energy grows, the photovoltaic industry, as an important component of clean energy, is experiencing an unprecedented wave of development. As the core part of the photovoltaic system, the performance of photovoltaic modules directly affects the power generation efficiency and long-term stability of the entire system. As the key packaging material of photovoltaic modules, photovoltaic films play a vital role in protecting cells, improving module power and extending service life.
[0003] However, there are some problems with traditional photovoltaic films during use, the most notable of which is the shrinkage problem. Shrinkage refers to the phenomenon that the film changes in size due to changes in environmental factors such as temperature and humidity during processing, use or storage. High shrinkage will not only lead to stress concentration inside the photovoltaic module, but may also cause serious problems such as cell breakage, delamination, and blistering, which will seriously affect the power generation efficiency and service life of the photovoltaic module.
[0004] Patent CN 114702919 B discloses a photovoltaic adhesive film and a preparation method thereof. The preparation raw materials of the method include EVA foamed particles, EVA particles B, a crosslinking agent, a co-crosslinking agent, a coupling agent, and EVA particles. The EVA foamed particles prepared by the invention can uniformly and quickly absorb the crosslinking agent and the co-crosslinking agent, thereby improving the production efficiency. At the same time, the adhesive film also has good mechanical properties and low shrinkage rate. However, the shrinkage rate of the photovoltaic adhesive film prepared by the method still has room for reduction, and its aging resistance and mechanical properties still have room for improvement. Summary of the invention
[0005] The purpose of the present invention is to provide a photovoltaic adhesive film with low shrinkage and a preparation method thereof, so as to solve the technical problems of high shrinkage, poor aging resistance and poor mechanical properties of the photovoltaic adhesive film in the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a photovoltaic adhesive film with a low shrinkage rate. The film is composed of the following components in parts by weight: 15-18 parts of ethylene-acrylic acid copolymer, 35-42 parts of ethylene-vinyl acetate copolymer, 1.5-1.8 parts of a crosslinking agent, 0.7-1.3 parts of a silane coupling agent, 1.1-2.7 parts of a composite light stabilizer, and 1.2-2.4 parts of a composite modifier. The composite light stabilizer is prepared from morpholine dichloride, N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, N-(4-aminophenyl)maleimide and pentaerythritol tetrakis(3-mercaptobutyrate), and the composite modifier is prepared from dimethylaminoethyl methacrylate, azobisisoheptonitrile and 4-cyano-4-(thiobenzoylthio)pentanoic acid.
[0008] Preferably, the crosslinking agent is one or more combinations of dicumyl peroxide, di-tert-butyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and peroxy-2-ethylhexyl tert-butyl carbonate; the silane coupling agent is one or more combinations of 3-methacryloxypropyltrimethoxysilane, n-dodecyltrimethoxysilane, and vinyltriacetoxysilane.
[0009] Preferably, the preparation method of the composite light stabilizer comprises the following steps:
[0010] Q1: Mix cyanuric chloride and xylene, then drop a xylene solution containing morpholine, control the drop time, continue the reaction after the drop addition is completed, add a sodium hydroxide aqueous solution after the reaction is completed, react at low temperature, stand for separation, wash the oil phase, distill under reduced pressure, filter the water phase, vacuum dry, mix, and obtain intermediate product 1;
[0011] Q2: Add intermediate product 1 and xylene to a container, heat after reaction and mixing, then dropwise add a mixed solution of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine and xylene, control the dropping time, add sodium hydroxide aqueous solution after the dropping is completed, raise the temperature to continue the reaction, and after the reaction is completed, stand and separate, wash, adjust the pH, and distill under reduced pressure to obtain intermediate product 2;
[0012] Q3: Add the intermediate product 2, xylene and distilled water into a container, then add formic acid, heat the reaction, add formaldehyde, continue to heat the reaction, cool down after the reaction, add sodium hydroxide aqueous solution, stand for separation, wash, adjust the pH, and distill under reduced pressure to obtain product 2;
[0013] Q4: Add N-(4-aminophenyl)maleimide, pentaerythritol tetrakis(3-mercaptobutyrate) and triethylamine to a container containing tetrahydrofuran, heat and react under a nitrogen atmosphere, and after the reaction is completed, cool, rotary evaporate, wash, centrifuge and vacuum dry to obtain product 3; mix product 2 and product 3 evenly to obtain a composite light stabilizer.
[0014] In the above process, product 2 and product 3 are mixed by physical stirring to prepare a composite light stabilizer, wherein the synthetic reaction formula of product 2 is as follows:
[0015]
[0016] The results of mass spectrometry analysis were: m / z: 614.54 (100.0%), 615.54 (38.7%), 616.54 (8.3%), 615.53 (3.0%);
[0017] The synthetic reaction formula of product 3 is as follows:
[0018]
[0019] m / z: 1296.36 (100.0%), 1297.37 (67.4%), 1298.37 (27.8%), 1298.36 (20.2%), 1299.36 (13.2%), 12 99.37 (8.5%), 1297.36 (6.2%), 1300.37 (5.3%), 1300.36 (2.6%), 1301.37 (1.5%), 1301.36 (1.0%).
[0020] Preferably, in Q1, the molar ratio of cyanuric chloride to morpholine is (1-2): (1.1-2.2), the dropping temperature is -5 to -8°C, the dropping time is 3 to 3.5 hours, the continued reaction time is 2 to 3 hours, the volume fraction of the sodium hydroxide aqueous solution is 10vt%, the low-temperature reaction temperature is -5 to -8°C, the reaction time is 0.5 to 1 hour, the oil phase is washed with ice water 2 to 3 times, the reduced pressure distillation temperature is 80 to 90°C, and the vacuum degree is 0.1 -0.2MPa; in Q2, the molar ratio of the intermediate product 1 and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine is (1-2): (2-5), the heating temperature is 80-85°C, the dropping time is 1-1.2h, the volume fraction of the sodium hydroxide aqueous solution is 10vt%, the temperature for continuing the reaction is 140-150°C, the reaction time is 8-10h, and the mixture is washed with a saturated sodium chloride solution for 3-5 times, and the pH is adjusted to 7.
[0021] Preferably, in Q3, the molar ratio of the intermediate product 2, formic acid and formaldehyde is (1-2): (2-5): (2-6), the purity of formic acid is 88%, the temperature of the reaction is 75-85°C, the reaction time is 1-1.3h, the temperature of the reaction is further increased to 90-95°C, the reaction time is 8-10h, the temperature is lowered to 25-30°C, the volume fraction of the sodium hydroxide aqueous solution is 10vt%, washed with distilled water 3-5 times, and the pH is adjusted to 7; in Q4, N- The molar ratio of (4-aminophenyl)maleimide, pentaerythritol tetrakis(3-mercaptobutyrate) and triethylamine is (1-2):(4-8):(0.8-1.5), the heating reaction temperature is 60-65°C, the reaction time is 12-14h, and the product is washed with methanol and toluene 3-5 times respectively. The vacuum drying temperature is 60-70°C, the time is 24-30h, the mass ratio of product 2 and product 3 is (2-4)g:(1-4)g, and the mixing time is 20-30min.
[0022] Preferably, the preparation method of the composite modifier comprises the following steps:
[0023] S1: purifying dimethylaminoethyl methacrylate through a basic alumina separation column, and then adding the purified dimethylaminoethyl methacrylate, azobisisoheptanenitrile, 4-cyano-4-(thiobenzoylthio)pentanoic acid and ethanol into a reaction container, mixing and stirring to obtain a mixture;
[0024] S2: The mixture is purged with nitrogen to remove oxygen, and then the mixture is placed in an oil bath for reaction. After the reaction is completed, the mixture is exposed to air and rapidly cooled in cold water to terminate the reaction, washed, and vacuum dried to obtain a composite modifier.
[0025] In the above process, 4-cyano-4-(thiobenzoylthio)pentanoic acid is used as a chain transfer agent, azobisisoheptanenitrile is used as an initiator, and dimethylaminoethyl methacrylate is reacted under the condition of ethanol as a solvent to prepare a composite modifier, wherein the synthetic reaction formula of the composite modifier is as follows:
[0026]
[0027] Preferably, in S1, the molar ratio of dimethylaminoethyl methacrylate, azobisisoheptanenitrile and 4-cyano-4-(thiobenzoylthio)pentanoic acid is (1-3): (0.01-0.03): (0.1-0.3), and the mixing time is 2-3 h.
[0028] Preferably, in S2, the nitrogen purge time is 30-45 min, the oil bath temperature is 70-75° C., the reaction time is 10-12 h, washing with n-hexane is 3-5 times, and the vacuum drying temperature is 50-60° C. for 24-30 h.
[0029] Preferably, the method for preparing the photovoltaic adhesive film with low shrinkage rate comprises the following steps:
[0030] Step (1): adding ethylene-acrylic acid copolymer to a double-roll mill, heating it to melt it, then adding a cross-linking agent to fully react with it, then adding ethylene-vinyl acetate copolymer, dynamically vulcanizing it and then unrolling it, and then adding the dynamically vulcanized product to a flat vulcanizer for preheating, exhausting, hot pressing, and cold pressing to obtain a composite resin;
[0031] Step (2): adding the composite resin, silane coupling agent, composite light stabilizer and composite modifier into a high-speed mixer, mixing evenly, heating and performing cast extrusion molding to prepare a photovoltaic film with a low shrinkage rate.
[0032] Preferably, in the step (1), the melting temperature of the ethylene-acrylic acid copolymer is 106.4°C, the acrylic acid content is 9.7wt%, the melting temperature of the ethylene-vinyl acetate is 76.0°C, the acrylic acid content is 26.0wt%, the heating melting temperature is 110-115°C, the dynamic vulcanization time is 3-5min, the temperature of the flat vulcanizer is 160-170°C, the preheating time is 8-10min, the exhaust is 3-5 times, the hot pressing time is 6-8min, and the cold pressing time is 8-10min; in the step (2), the speed of the high-speed stirrer is 1000-1200rpm, the stirring time is 30-45min, and the heating casting temperature is 160-170°C.
[0033] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0034] 1. The present invention first uses cyanuric chloride, morpholine, N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, formic acid and sodium hydroxide as raw materials to prepare product 2, then uses N-(4-aminophenyl)maleimide, pentaerythritol tetrakis(3-mercaptobutyrate) and triethylamine as raw materials to obtain product 3, physically mixes product 2 with product 3 to obtain a composite light stabilizer, and simultaneously uses dimethylaminoethyl methacrylate, azobisisoheptanenitrile and 4-cyano-4-(thiobenzoylthio)pentanoic acid to prepare a composite modifier, and simultaneously adds the composite light stabilizer and the composite modifier into the composite resin, so that the prepared photovoltaic adhesive film has low shrinkage, excellent mechanical properties and aging resistance.
[0035] 2. The present invention uses cyanuric chloride, morpholine, N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, formic acid, sodium hydroxide, N-(4-aminophenyl)maleimide and pentaerythritol tetrakis(3-mercaptobutyrate) as raw materials to prepare a composite light stabilizer, which is added to the photovoltaic adhesive film to effectively improve its aging resistance and mechanical properties. The composite light stabilizer contains a piperazine structure, which can effectively absorb or reflect ultraviolet light and reduce the direct exposure of ultraviolet light to the photovoltaic film. N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, as a free radical scavenger, can capture free radicals generated under ultraviolet light to prevent or delay the photodegradation process; N-(4-aminophenyl)maleimide, as an ultraviolet absorber, can absorb or reflect ultraviolet light and reduce the photodegradation process. The anti-ultraviolet ability of product 2 and the antioxidant ability of product 3 play a synergistic role and jointly promote the composite light stabilizer to improve the aging resistance of the photovoltaic film; at the same time, the groups in the composite light stabilizer can undergo cross-linking reactions with the chains in the photovoltaic film, enhance the interaction between polymer chains, and improve the mechanical properties and aging resistance of the photovoltaic film.
[0036] 3. The present invention uses dimethylaminoethyl methacrylate, azobisisoheptanenitrile and 4-cyano-4-(thiobenzoylthio)pentanoic acid as raw materials to prepare a composite modifier, which can be added to the photovoltaic film to effectively reduce its shrinkage and improve its mechanical properties. The chain transfer agent component in the composite modifier can effectively control the chain growth during the polymerization process, making the length distribution of the polymer chain more uniform and reducing the difference in the proportion of long chains and short chains. The uniform chain length distribution means less internal stress and shrinkage driving force, which helps to reduce the shrinkage of the photovoltaic film during the curing process. The composite modifier also has the function of promoting cross-linking reaction. By increasing the cross-linking points between polymer chains, the internal network structure stability of the photovoltaic film is improved, and the shrinkage rate is further reduced. At the same time, the formed cross-linking points can also increase the interaction force between polymer chains, so that the photovoltaic film can better resist deformation and damage when subjected to external forces, thereby improving the mechanical properties of the photovoltaic film. DETAILED DESCRIPTION
[0037] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment discloses a method for preparing a composite light stabilizer, comprising the following steps:
[0040] Q1: 15 g of cyanuric chloride was mixed with 70 g of xylene, and then 165 g of a xylene solution containing 7.8 g of morpholine was added dropwise at -8 °C for 3 h. After the addition was completed, the reaction was continued for 2 h. After the reaction was completed, 24 g of a 10% by volume sodium hydroxide aqueous solution was added, and the reaction was carried out at -5 °C for 1 h. The mixture was allowed to stand for separation, and the oil phase was washed with ice water for 3 times. The mixture was distilled under reduced pressure at 85 °C and 0.1 MPa, and the aqueous phase was filtered, vacuum dried, and mixed to obtain an intermediate product 1.
[0041] Q2: 18.8g of intermediate product 1 and 188g of xylene were added to a container, the mixture was reacted and heated to 80°C, and then a mixed solution of 39.89g of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine and 60g of xylene was added dropwise, and the dropping time was controlled to be 1h. After the dropping was completed, 60g of a 10vt% sodium hydroxide aqueous solution was added, and the temperature was raised to 140°C and the reaction was continued for 8h. After the reaction was completed, the liquid was allowed to stand and separated, and the mixture was washed with a saturated sodium chloride solution for 3 times, the pH was adjusted to 7, and the mixture was distilled under reduced pressure to obtain an intermediate product 2;
[0042] Q3: 4.40g of intermediate product 2, 22g of xylene and 6g of distilled water were added to a container, followed by 0.77g of formic acid with a purity of 88%, and the temperature was raised to 85°C for reaction for 1h, followed by 0.58g of formaldehyde, and the temperature was further raised to 90°C for reaction for 10h. After the reaction was completed, the temperature was lowered to 30°C, and a 10vt% sodium hydroxide aqueous solution was added, and the solution was allowed to stand for separation, and the solution was washed with distilled water for 3 times, the pH was adjusted to 7, and the product 2 was obtained by vacuum distillation.
[0043] Q4: Add 6.5 g of N-(4-aminophenyl)maleimide, 9.92 g of pentaerythritol tetrakis(3-mercaptobutyrate) and 1.02 g of triethylamine into a container containing 150 mL of tetrahydrofuran, and react at 65°C for 12 h under a nitrogen atmosphere. After the reaction, cool, rotary evaporate, wash with methanol and toluene three times respectively, centrifuge, and vacuum dry at 70°C for 24 h to obtain product 3; mix 3 g of product 2 with 2.5 g of product 3 for 30 min to obtain a composite light stabilizer.
[0044] This embodiment discloses a method for preparing a composite modifier, comprising the following steps:
[0045] S1: purify dimethylaminoethyl methacrylate through a basic alumina separation column, then add 25.12 g of the purified dimethylaminoethyl methacrylate, 0.40 g of azobisisoheptanenitrile, 4.47 g of 4-cyano-4-(thiobenzoylthio)pentanoic acid and 13 mL of ethanol into a reaction container, mix and stir for 3 h to obtain a mixture;
[0046] S2: The mixture was purged with nitrogen for 45 minutes to remove oxygen, and then the mixture was placed in a 75°C oil bath for reaction for 12 hours. After the reaction, the mixture was exposed to air and quickly cooled in cold water to terminate the reaction, washed with n-hexane for 5 times, and vacuum dried at 60°C for 24 hours to obtain a composite modifier.
[0047] The present embodiment discloses a photovoltaic adhesive film with a low shrinkage rate, which is composed of the following ingredients in parts by weight: 16.5 parts of ethylene-acrylic acid copolymer, 38.5 parts of ethylene-vinyl acetate copolymer, 1.7 parts of dicumyl peroxide, 1 part of 3-methacryloxypropyltrimethoxysilane, 1.9 parts of composite light stabilizer, and 1.8 parts of composite modifier.
[0048] This embodiment discloses a method for preparing a photovoltaic adhesive film with a low shrinkage rate, comprising the following steps:
[0049] Step (1): adding an ethylene-acrylic acid copolymer having a melting temperature of 106.4° C. and an acrylic acid content of 9.7 wt % to a double-roll mill, melting it at 115° C., then adding dicumyl peroxide to fully react with it, then adding an ethylene-vinyl acetate copolymer having a melting temperature of 76.0° C. and an acrylic acid content of 26.0 wt %, dynamically vulcanizing for 3 minutes, and then putting the dynamically vulcanized product into a flat vulcanizer at 170° C., preheating for 10 minutes, exhausting 5 times, hot pressing for 8 minutes, and cold pressing for 10 minutes to obtain a composite resin;
[0050] Step (2): adding the composite resin, 3-methacryloxypropyltrimethoxysilane, the composite light stabilizer and the composite modifier into a 1200 rpm mixer, mixing for 45 minutes, and then heating at 165° C. for cast extrusion molding to prepare a photovoltaic film with a low shrinkage rate.
[0051] Example 2
[0052] This embodiment discloses a method for preparing a composite light stabilizer, comprising the following steps:
[0053] Q1: 10 g of cyanuric chloride was mixed with 70 g of xylene, and then 165 g of a xylene solution containing 10.4 g of morpholine was added dropwise at -8 °C for 3 h. After the addition was completed, the reaction was continued for 2 h. After the reaction was completed, 24 g of a 10% by volume sodium hydroxide aqueous solution was added, and the reaction was carried out at -5 °C for 1 h. The mixture was allowed to stand for separation, and the oil phase was washed with ice water for 3 times. The mixture was distilled under reduced pressure at 85 °C and 0.1 MPa, and the aqueous phase was filtered, vacuum dried, and mixed to obtain an intermediate product 1.
[0054] Q2: 12.5 g of intermediate product 1 and 188 g of xylene were added to a container, the mixture was reacted and heated to 80°C, and then a mixed solution of 23.17 g of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine and 60 g of xylene was added dropwise, and the dropping time was controlled to be 1 h. After the dropping was completed, 60 g of a 10 vt% sodium hydroxide aqueous solution was added, and the temperature was raised to 140°C and the reaction was continued for 8 h. After the reaction was completed, the liquid was allowed to stand and separated, and the mixture was washed with a saturated sodium chloride solution for 3 times, the pH was adjusted to 7, and the mixture was distilled under reduced pressure to obtain intermediate product 2;
[0055] Q3: 2.93g of intermediate product 2, 22g of xylene and 6g of distilled water were added to a container, followed by 0.44g of formic acid with a purity of 88%, and the temperature was raised to 85°C for reaction for 1h, followed by 0.29g of formaldehyde, and the temperature was further raised to 90°C for reaction for 10h. After the reaction was completed, the temperature was lowered to 30°C, and a 10vt% sodium hydroxide aqueous solution was added, and the solution was allowed to stand for separation, and the solution was washed with distilled water for 3 times, the pH was adjusted to 7, and the product 2 was obtained by vacuum distillation.
[0056] Q4: Add 4.3g N-(4-aminophenyl)maleimide, 6.61g pentaerythritol tetrakis(3-mercaptobutyrate) and 0.71g triethylamine into a container containing 150mL tetrahydrofuran, react at 65°C for 12h under nitrogen atmosphere, cool after reaction, rotary evaporate, wash with methanol and toluene three times respectively, centrifuge, and vacuum dry at 70°C for 24h to obtain product 3; mix 2g product 2 with 1g product 3 for 30min to obtain a composite light stabilizer.
[0057] This embodiment discloses a method for preparing a composite modifier, comprising the following steps:
[0058] S1: purify dimethylaminoethyl methacrylate through a basic alumina separation column, then add 12.56 g of the purified dimethylaminoethyl methacrylate, 0.19 g of azobisisoheptanenitrile, 2.23 g of 4-cyano-4-(thiobenzoylthio)pentanoic acid and 13 mL of ethanol into a reaction container, mix and stir for 3 h to obtain a mixture;
[0059] S2: The mixture was purged with nitrogen for 45 minutes to remove oxygen, and then the mixture was placed in a 75°C oil bath for reaction for 12 hours. After the reaction, the mixture was exposed to air and quickly cooled in cold water to terminate the reaction, washed with n-hexane for 5 times, and vacuum dried at 60°C for 24 hours to obtain a composite modifier.
[0060] The present embodiment discloses a photovoltaic adhesive film with a low shrinkage rate, which is composed of the following ingredients in parts by weight: 15 parts of ethylene-acrylic acid copolymer, 35 parts of ethylene-vinyl acetate copolymer, 1.5 parts of dicumyl peroxide, 0.7 parts of 3-methacryloxypropyltrimethoxysilane, 1.1 parts of composite light stabilizer, and 1.2 parts of composite modifier.
[0061] This embodiment discloses a method for preparing a photovoltaic adhesive film with a low shrinkage rate, comprising the following steps:
[0062] Step (1): adding an ethylene-acrylic acid copolymer having a melting temperature of 106.4° C. and an acrylic acid content of 9.7 wt % to a double-roll mill, melting it at 115° C., then adding dicumyl peroxide to fully react with it, then adding an ethylene-vinyl acetate copolymer having a melting temperature of 76.0° C. and an acrylic acid content of 26.0 wt %, dynamically vulcanizing for 3 minutes, and then putting the dynamically vulcanized product into a flat vulcanizer at 170° C., preheating for 10 minutes, exhausting 5 times, hot pressing for 8 minutes, and cold pressing for 10 minutes to obtain a composite resin;
[0063] Step (2): adding the composite resin, 3-methacryloxypropyltrimethoxysilane, the composite light stabilizer and the composite modifier into a 1200 rpm mixer, mixing for 45 minutes, and then heating at 165° C. for cast extrusion molding to prepare a photovoltaic film with a low shrinkage rate.
[0064] Example 3
[0065] This embodiment discloses a method for preparing a composite light stabilizer, comprising the following steps:
[0066] Q1: 20 g of cyanuric chloride and 70 g of xylene were mixed, and then 165 g of a xylene solution containing 5.2 g of morpholine was added dropwise at -8 °C for 3 h. After the addition was completed, the reaction was continued for 2 h. After the reaction was completed, 24 g of a 10% by volume sodium hydroxide aqueous solution was added, and the reaction was carried out at -5 °C for 1 h. The mixture was allowed to stand for separation, and the oil phase was washed with ice water for 3 times. The mixture was distilled under reduced pressure at 85 °C and 0.1 MPa, and the aqueous phase was filtered, vacuum dried, and mixed to obtain an intermediate product 1.
[0067] Q2: 25.1g of intermediate product 1 and 188g of xylene were added to a container, and the mixture was heated to 80°C after reaction, and then a mixed solution of 56.60g of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine and 60g of xylene was added dropwise, and the dropping time was controlled to be 1h. After the dropping was completed, 60g of a 10vt% sodium hydroxide aqueous solution was added, and the temperature was raised to 140°C and the reaction was continued for 8h. After the reaction was completed, the liquid was allowed to stand and separated, and the mixture was washed with a saturated sodium chloride solution for 3 times, the pH was adjusted to 7, and the mixture was distilled under reduced pressure to obtain an intermediate product 2;
[0068] Q3: 5.86g of intermediate product 2, 22g of xylene and 6g of distilled water were added to a container, followed by 1.10g of formic acid with a purity of 88%, and the temperature was raised to 85°C for reaction for 1h, followed by 0.86g of formaldehyde, and the temperature was further raised to 90°C for reaction for 10h. After the reaction was completed, the temperature was lowered to 30°C, and a 10vt% sodium hydroxide aqueous solution was added, and the solution was allowed to stand for separation, and the solution was washed with distilled water for 3 times, the pH was adjusted to 7, and the product 2 was obtained by distillation under reduced pressure;
[0069] Q4: 8.6 g of N-(4-aminophenyl)maleimide, 13.23 g of pentaerythritol tetrakis(3-mercaptobutyrate) and 1.33 g of triethylamine were added to a container containing 150 mL of tetrahydrofuran, and reacted at 65°C for 12 h under a nitrogen atmosphere. After the reaction, the mixture was cooled, rotary evaporated, washed with methanol and toluene three times respectively, centrifuged, and vacuum dried at 70°C for 24 h to obtain product 3; 4 g of product 2 was mixed with 4 g of product 3 for 30 min to obtain a composite light stabilizer.
[0070] This embodiment discloses a method for preparing a composite modifier, comprising the following steps:
[0071] S1: purify dimethylaminoethyl methacrylate through a basic alumina separation column, then add 37.68 g of the purified dimethylaminoethyl methacrylate, 0.60 g of azobisisoheptanenitrile, 6.70 g of 4-cyano-4-(thiobenzoylthio)pentanoic acid and 13 mL of ethanol into a reaction container, mix and stir for 3 h to obtain a mixture;
[0072] S2: The mixture was purged with nitrogen for 45 minutes to remove oxygen, and then the mixture was placed in a 75°C oil bath for reaction for 12 hours. After the reaction, the mixture was exposed to air and quickly cooled in cold water to terminate the reaction, washed with n-hexane for 5 times, and vacuum dried at 60°C for 24 hours to obtain a composite modifier.
[0073] The present embodiment discloses a photovoltaic adhesive film with a low shrinkage rate, which is composed of the following ingredients in parts by weight: 18 parts of ethylene-acrylic acid copolymer, 42 parts of ethylene-vinyl acetate copolymer, 1.8 parts of dicumyl peroxide, 1.3 parts of 3-methacryloxypropyltrimethoxysilane, 2.7 parts of composite light stabilizer, and 2.4 parts of composite modifier.
[0074] This embodiment discloses a method for preparing a photovoltaic adhesive film with a low shrinkage rate, comprising the following steps:
[0075] Step (1): adding an ethylene-acrylic acid copolymer having a melting temperature of 106.4° C. and an acrylic acid content of 9.7 wt % to a double-roll mill, melting it at 115° C., then adding dicumyl peroxide to fully react with it, then adding an ethylene-vinyl acetate copolymer having a melting temperature of 76.0° C. and an acrylic acid content of 26.0 wt %, dynamically vulcanizing for 3 minutes, and then putting the dynamically vulcanized product into a flat vulcanizer at 170° C., preheating for 10 minutes, exhausting 5 times, hot pressing for 8 minutes, and cold pressing for 10 minutes to obtain a composite resin;
[0076] Step (2): adding the composite resin, 3-methacryloxypropyltrimethoxysilane, the composite light stabilizer and the composite modifier into a 1200 rpm mixer, mixing for 45 minutes, and then heating at 165° C. for cast extrusion molding to prepare a photovoltaic film with a low shrinkage rate.
[0077] Example 4
[0078] This embodiment discloses a method for preparing a composite light stabilizer, comprising the following steps:
[0079] Q1: 12g of cyanuric chloride was mixed with 70g of xylene, and then 165g of a xylene solution containing 7.5g of morpholine was added dropwise at -8°C for 3h. After the addition was completed, the reaction was continued for 2h. After the reaction was completed, 24g of a 10vt% sodium hydroxide aqueous solution was added, and the reaction was carried out at -5°C for 1h. The mixture was allowed to stand for separation, and the oil phase was washed with ice water for 3 times. The mixture was distilled under reduced pressure at 85°C and 0.1MPa, and the aqueous phase was filtered, dried in vacuo, and mixed to obtain an intermediate product 1.
[0080] Q2: 15.4 g of intermediate product 1 and 188 g of xylene were added to a container, the mixture was reacted and heated to 80°C, and then a mixed solution of 31.5 g of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine and 60 g of xylene was added dropwise, and the dropping time was controlled to be 1 h. After the dropping was completed, 60 g of a 10 vt% sodium hydroxide aqueous solution was added, and the temperature was raised to 140°C and the reaction was continued for 8 h. After the reaction was completed, the liquid was allowed to stand and separated, and the mixture was washed with a saturated sodium chloride solution for 3 times, the pH was adjusted to 7, and the mixture was distilled under reduced pressure to obtain an intermediate product 2;
[0081] Q3: 3.65g of intermediate product 2, 22g of xylene and 6g of distilled water were added to a container, followed by 0.94g of formic acid with a purity of 88%, and the temperature was raised to 85°C for reaction for 1h, followed by 0.44g of formaldehyde, and the temperature was further raised to 90°C for reaction for 10h. After the reaction was completed, the temperature was lowered to 30°C, and a 10vt% sodium hydroxide aqueous solution was added, and the solution was allowed to stand for separation, and the solution was washed with distilled water for 3 times, the pH was adjusted to 7, and the product 2 was obtained by vacuum distillation.
[0082] Q4: 5.4 g N-(4-aminophenyl)maleimide, 11.58 g pentaerythritol tetrakis(3-mercaptobutyrate) and 1.18 g triethylamine were added to a container containing 150 mL tetrahydrofuran, and reacted at 65°C for 12 h under a nitrogen atmosphere. After the reaction, the mixture was cooled, rotary evaporated, washed with methanol and toluene three times respectively, centrifuged, and vacuum dried at 70°C for 24 h to obtain product 3; 2.5 g product 2 was mixed with 2 g product 3 for 30 min to obtain a composite light stabilizer.
[0083] This embodiment discloses a method for preparing a composite modifier, comprising the following steps:
[0084] S1: purify dimethylaminoethyl methacrylate through a basic alumina separation column, then add 18.84 g of the purified dimethylaminoethyl methacrylate, 0.29 g of azobisisoheptanenitrile, 3.35 g of 4-cyano-4-(thiobenzoylthio)pentanoic acid and 13 mL of ethanol into a reaction container, mix and stir for 3 h to obtain a mixture;
[0085] S2: The mixture was purged with nitrogen for 45 minutes to remove oxygen, and then the mixture was placed in a 75°C oil bath for reaction for 12 hours. After the reaction, the mixture was exposed to air and quickly cooled in cold water to terminate the reaction, washed with n-hexane for 5 times, and vacuum dried at 60°C for 24 hours to obtain a composite modifier.
[0086] The present embodiment discloses a photovoltaic adhesive film with a low shrinkage rate, which is composed of the following ingredients in parts by weight: 16.5 parts of ethylene-acrylic acid copolymer, 38.5 parts of ethylene-vinyl acetate copolymer, 1.7 parts of dicumyl peroxide, 1 part of 3-methacryloxypropyltrimethoxysilane, 1.9 parts of composite light stabilizer, and 1.8 parts of composite modifier.
[0087] This embodiment discloses a method for preparing a photovoltaic adhesive film with a low shrinkage rate, comprising the following steps:
[0088] Step (1): adding an ethylene-acrylic acid copolymer having a melting temperature of 106.4° C. and an acrylic acid content of 9.7 wt % to a double-roll mill, melting it at 115° C., then adding dicumyl peroxide to fully react with it, then adding an ethylene-vinyl acetate copolymer having a melting temperature of 76.0° C. and an acrylic acid content of 26.0 wt %, dynamically vulcanizing for 3 minutes, and then putting the dynamically vulcanized product into a flat vulcanizer at 170° C., preheating for 10 minutes, exhausting 5 times, hot pressing for 8 minutes, and cold pressing for 10 minutes to obtain a composite resin;
[0089] Step (2): adding the composite resin, 3-methacryloxypropyltrimethoxysilane, the composite light stabilizer and the composite modifier into a 1200 rpm mixer, mixing for 45 minutes, and then heating at 165° C. for cast extrusion molding to prepare a photovoltaic film with a low shrinkage rate.
[0090] Comparative Example 1
[0091] Comparative Example 1 Compared with Example 1, in the process of preparing the composite light stabilizer in Comparative Example 1, no cyanuric chloride was added, and other conditions remained unchanged.
[0092] Comparative Example 2
[0093] Comparative Example 2 Compared with Example 1, in the process of preparing the composite light stabilizer in Comparative Example 2, N-butyl-2,2,6,6-tetramethyl-4-piperidinamine was not added, and other conditions remained unchanged.
[0094] Comparative Example 3
[0095] Comparative Example 3 Compared with Example 1, in the process of preparing the composite modifier in Comparative Example 3, dimethylaminoethyl methacrylate was not added, and other conditions remained unchanged.
[0096] Comparative Example 4
[0097] Comparative Example 4 Compared with Example 1, in the process of preparing the composite modifier in Comparative Example 4, no 4-cyano-4-(thiobenzoylthio)pentanoic acid was added, and other conditions remained unchanged.
[0098] Comparative Example 5
[0099] Comparative Example 5 Compared with Example 1, in the process of preparing the photovoltaic adhesive film in Comparative Example 5, no composite light stabilizer is added, and other conditions remain unchanged.
[0100] Comparative Example 6
[0101] Compared with Example 1, in Comparative Example 6, during the preparation of the photovoltaic adhesive film, no composite modifier was added, and other conditions remained unchanged.
[0102] The photovoltaic adhesive films prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to performance tests. The tensile properties of the samples were tested according to GB / T528-2009. The obtained samples were placed in a DHG-9030A type blast drying oven for aging test. The aging temperature was 50°C, the aging time was 15 days, the ultraviolet light came from UVA-340, and the aging coefficient K was used to evaluate the changes in the mechanical properties of the samples after aging. K=δ2ε2 / δ1ε1, δ2 is the tensile strength after aging, ε2 is the elongation at break after aging, δ1 is the tensile strength before aging, and ε1 is the elongation at break before aging. The shrinkage rate of the samples was tested according to GB / T 29848-2018, and the test results are shown in Table 1:
[0103] Table 1
[0104]
[0105] It can be seen from the test results in Table 1 that the photovoltaic adhesive films prepared in Examples 1-4 of the present invention have excellent mechanical properties, aging resistance and low shrinkage. From the comparison between comparative example 1 and examples 1-4, it can be seen that the addition of cyanuric chloride can make the photovoltaic adhesive film have excellent mechanical properties and aging resistance; from the comparison between comparative example 2 and examples 1-4, it can be seen that the addition of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine can make the photovoltaic adhesive film have excellent mechanical properties and aging resistance; from the comparison between comparative example 3 and examples 1-4, it can be seen that the addition of dimethylaminoethyl methacrylate can make the photovoltaic adhesive film have excellent mechanical properties and low shrinkage; from the comparison between comparative example 4 and examples 1-4, it can be seen that the addition of 4-cyano-4-(thiobenzoylthio)pentanoic acid can make the photovoltaic adhesive film have excellent mechanical properties and low shrinkage; from the comparison between comparative example 5 and examples 1-4, it can be seen that the addition of a composite light stabilizer can make the photovoltaic adhesive film have excellent mechanical properties and aging resistance; from the comparison between comparative example 6 and examples 1-4, it can be seen that the addition of a composite light stabilizer can make the photovoltaic adhesive film have excellent mechanical properties and low shrinkage.
[0106] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0107] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Low shrinkage photovoltaic film, characterized in that: The invention is composed of the following components in parts by weight: 15-18 parts of ethylene-acrylic acid copolymer, 35-42 parts of ethylene-vinyl acetate copolymer, 1.5-1.8 parts of a crosslinking agent, 0.7-1.3 parts of a silane coupling agent, 1.1-2.7 parts of a composite light stabilizer, and 1.2-2.4 parts of a composite modifier, wherein the composite light stabilizer is prepared from morpholine dichloride, N-butyl-2,2,6,6-tetramethyl-4-piperidinamine, N-(4-aminophenyl)maleimide and pentaerythritol tetrakis(3-mercaptobutyrate), and the composite modifier is prepared from dimethylaminoethyl methacrylate, azobisisoheptonitrile and 4-cyano-4-(thiobenzoylthio)pentanoic acid; The preparation method of the composite light stabilizer comprises the following steps: Q1: Mix cyanuric chloride and xylene, then drop a xylene solution containing morpholine, control the drop time, continue the reaction after the drop addition is completed, add a sodium hydroxide aqueous solution after the reaction is completed, react at low temperature, stand for separation, wash the oil phase, distill under reduced pressure, filter the water phase, vacuum dry, mix, and obtain intermediate product 1; Q2: Add intermediate product 1 and xylene to a container, heat after reaction and mixing, then dropwise add a mixed solution of N-butyl-2,2,6,6-tetramethyl-4-piperidinamine and xylene, control the dropping time, add sodium hydroxide aqueous solution after the dropping is completed, raise the temperature to continue the reaction, and after the reaction is completed, stand and separate, wash, adjust the pH, and distill under reduced pressure to obtain intermediate product 2; Q3: Add the intermediate product 2, xylene and distilled water into a container, then add formic acid, heat the reaction, add formaldehyde, continue to heat the reaction, cool down after the reaction, add sodium hydroxide aqueous solution, stand for separation, wash, adjust the pH, and distill under reduced pressure to obtain product 2; Q4: Add N-(4-aminophenyl)maleimide, pentaerythritol tetrakis(3-mercaptobutyrate) and triethylamine into a container containing tetrahydrofuran, heat and react under a nitrogen atmosphere. After the reaction is completed, cool, rotary evaporate, wash, centrifuge and vacuum dry to obtain product 3; mix product 2 and product 3 evenly to obtain a composite light stabilizer.
2. The low shrinkage photovoltaic adhesive film according to claim 1, characterized in that: The crosslinking agent is one or more combinations of dicumyl peroxide, di-tert-butyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and peroxy-2-ethylhexyl tert-butyl carbonate; the silane coupling agent is one or more combinations of 3-methacryloxypropyltrimethoxysilane, n-dodecyltrimethoxysilane, and vinyltriacetoxysilane.
3. The low shrinkage photovoltaic adhesive film according to claim 1, characterized in that: In the Q1, the molar ratio of cyanuric chloride to morpholine is (1-2): (1.1-2.2), the dropping temperature is -5~-8°C, the dropping time is 3-3.5h, the continued reaction time is 2-3h, the volume fraction of the sodium hydroxide aqueous solution is 10vt%, the low-temperature reaction temperature is -5~-8°C, the reaction time is 0.5-1h, the oil phase is washed with ice water 2-3 times, the reduced pressure distillation temperature is 80-90°C, and the vacuum degree is 0.1-0 .2MPa; in Q2, the molar ratio of the intermediate product 1 and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine is (1-2): (2-5), the heating temperature is 80-85°C, the dropping time is 1-1.2h, the volume fraction of the sodium hydroxide aqueous solution is 10vt%, the temperature for continuing the reaction is 140-150°C, the reaction time is 8-10h, and the reaction is washed with saturated sodium chloride solution for 3-5 times, and the pH is adjusted to 7.
4. The low shrinkage photovoltaic adhesive film according to claim 1, characterized in that: In the Q3, the molar ratio of the intermediate product 2, formic acid and formaldehyde is (1-2): (2-5): (2-6), the purity of formic acid is 88%, the temperature of the reaction is 75-85°C, the reaction time is 1-1.3h, the temperature of the reaction is further increased to 90-95°C, the reaction time is 8-10h, the temperature is cooled to 25-30°C, the volume fraction of the sodium hydroxide aqueous solution is 10vt%, and the solution is washed with distilled water for 3-5 times, and the pH is adjusted to 7; in the Q4, N-(4- The molar ratio of aminophenyl)maleimide, pentaerythritol tetrakis(3-mercaptobutyrate) and triethylamine is (1-2):(4-8):(0.8-1.5), the heating reaction temperature is 60-65°C, the reaction time is 12-14h, washed with methanol and toluene 3-5 times respectively, the vacuum drying temperature is 60-70°C, the time is 24-30h, the mass ratio of product 2 and product 3 is (2-4)g:(1-4)g, and the mixing time is 20-30min.
5. The low shrinkage photovoltaic adhesive film according to claim 1, characterized in that: The preparation method of the composite modifier comprises the following steps: S1: purifying dimethylaminoethyl methacrylate through a basic alumina separation column, then adding the purified dimethylaminoethyl methacrylate, azobisisoheptanenitrile, 4-cyano-4-(thiobenzoylthio)pentanoic acid and ethanol into a reaction container, mixing and stirring to obtain a mixture; S2: The mixture is purged with nitrogen to remove oxygen, and then the mixture is placed in an oil bath for reaction. After the reaction is completed, the mixture is exposed to air and rapidly cooled in cold water to terminate the reaction, washed, and vacuum dried to obtain a composite modifier.
6. The low shrinkage photovoltaic adhesive film according to claim 5, characterized in that: In the S1, the molar ratio of dimethylaminoethyl methacrylate, azobisisoheptanenitrile and 4-cyano-4-(thiobenzoylthio)pentanoic acid is (1-3): (0.01-0.03): (0.1-0.3), and the mixing and stirring time is 2-3 hours.
7. The low shrinkage photovoltaic adhesive film according to claim 5, characterized in that: In S2, the nitrogen purge time is 30-45 min, the oil bath temperature is 70-75° C., the reaction time is 10-12 h, the product is washed with n-hexane 3-5 times, and the vacuum drying temperature is 50-60° C. for 24-30 h.
8. The method for preparing a photovoltaic adhesive film with low shrinkage as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step (1): adding ethylene-acrylic acid copolymer to a double-roll mill, heating it to melt it, then adding a cross-linking agent to fully react with it, then adding ethylene-vinyl acetate copolymer, dynamically vulcanizing it and then unrolling it, then adding the dynamically vulcanized product to a flat vulcanizer for preheating, exhausting, hot pressing, and cold pressing to obtain a composite resin; Step (2): adding the composite resin, silane coupling agent, composite light stabilizer and composite modifier into a high-speed mixer, mixing evenly, heating and performing cast extrusion molding to prepare a photovoltaic film with a low shrinkage rate.
9. The method for preparing a photovoltaic adhesive film with a low shrinkage rate according to claim 8, characterized in that: In the step (1), the melting temperature of the ethylene-acrylic acid copolymer is 106.4°C, the acrylic acid content is 9.7wt%, the melting temperature of the ethylene-vinyl acetate copolymer is 76.0°C, the vinyl acetate content is 26.0wt%, the heating melting temperature is 110-115°C, the dynamic vulcanization time is 3-5min, the temperature of the flat vulcanizer is 160-170°C, the preheating time is 8-10min, the exhaust is 3-5 times, the hot pressing time is 6-8min, and the cold pressing time is 8-10min; in the step (2), the speed of the high-speed stirrer is 1000-1200rpm, the stirring time is 30-45min, and the heating casting temperature is 160-170°C.
Citation Information
Patent Citations
Preparation method for POSS / PDMAEMA organic / inorganic hybrid material according to thiol-ene click chemistry method
CN104558321A
N-substituted triazine hindered amine light stabilizer and preparation method and application thereof
CN109134928A